A Study to Assess the Effectiveness of Structured Teaching Program on Knowledge Regarding Menstrual Hygiene Among the Adolescent Girls in Kanpur - Divya Dwivedi; Shahin; Samreen Sheikh; Shruti Katiyar; Pranjali Singh; Shivani Tiwari; Aditya Singh (International Journal of Midwifery Nursing And Practices, 2025)
Background: Adolescent girls are less aware or unaware about menstrual hygiene and diseases occurring from unhygienic menstrual practice. Therefore, the present study aims to assess the effectiveness of a structured teaching program in improving menstrual hygiene knowledge. Method: The study utilized a quasi-experimental, one-group pretest-posttest design, with 40 adolescent girls chosen as participants using a simple random sampling method. Result: The mean pretest knowledge score was 1.90, while the mean posttest knowledge score showed that all 40 (100%) adolescent girls had adequate knowledge after the intervention. The paired t-test yielded a value of 14.022, which is greater than the table value of 2.02 at 39 degrees of freedom, indicating a statistically significant improvement at the 0.05 level. These results suggest that the structured teaching program successfully improved adolescent girls’ knowledge of menstrual hygiene. The study also found a significant relationship between knowledge levels and specific demographic factors, including the duration of menstrual bleeding. Conclusion: Study concluded that the knowledge of adolescent girls was adequate about menstrual hygiene.
Keywords: Adolescent girls; Menstrual hygiene; knowledge improvement; quasi-experimental study; structured teaching program